Panduan am ramalan hasil awal kelapa sawit di projek tanam semula FASSB - Shuhaimi Shamsudin (2014)
Under good management practices, early high yields are achievable. To forecast early yields, especially for the first two years of production, in the replanting projects under FASSB, a technique adapted from the "bunch census" method in oil palm breeding was used. This paper outlines the methodology and shows the close relationship between the forecasted and actual yield over the first six months in Phase 2 of FASSB's Ulu Jempol Project.